Ex situ heart magnetic resonance imaging and angiography: feasibility study for forensic purposes. (June 2021) - Cafarelli, Francesco Pio; Macarini, Luca; Cipolloni, Luigi; Maglietta, Francesca; Guglielmi, Giuseppe; Sessa, Francesco; Pennisi, Antonio; Cantatore, Santina; Bertozzi, Giuseppe
Abstract: Objectives: The aim of this feasibility study was to investigate the potential role of ex-situ heart MRI and angiography (MRA) after formalin fixation. Materials and Methods: The heart of a 22-year-old dead male was explanted and placed inside a container, filled with 10% formalin solution. MRI was performed with 1.5 T scanner at three different times (24 hours, 7 days and 30 days). The examination protocol included eight sequences. Two readers completed image analyses after randomization and blinded to both cause of death and examination timing. Results: Both readers reported no significant differences among the three groups of images and no signs of pathological alterations, even when analyzing coronaries, performed without an additional contrast agent. Histological examinations confirmed these results. Conclusions: This study demonstrates the reliability of an MRI protocol to study an ex situ fixed-heart, not influenced by acquisition timing. Moreover, MRA allows coronary arteries to be easily studied thanks to the formalin solution as contrast.